Behaviour problems of children with ASD and perceived stress in their caregivers: The moderating role of trait emotional intelligence?. (August 2016) - Lovell, Brian; Wetherell, Mark A.
Highlights: A direct effect of CBP and TEI on caregivers' PSS was observed. TEI did not moderate the CBP-PSS relationship. Higher CBP and lower TEI are risk factors for psychological distress in caregivers. Abstract: Background: Psychological distress in caregivers of children with autism spectrum disorder (ASD) has been shown to vary according to characteristics of the care recipient, especially their behaviour problems. Trait emotional intelligence (TEI), which has been linked with subjective reports of distress in familial caregivers, has also been shown to predict behaviour problems in the care recipient. This study is, we believe, first to examine whether TEI might moderate the effect of child behaviour problems (CBP) on caregivers' psychological functioning. Method: A sample of 118 parents of children with clinically verified ASD was asked to complete an online survey assessing: (a) TEI, (b) CBP and (c) perceived stress scores (PSS). The SPSS PROCESS macro (model 1) with bootstrapping was used to determine whether CBP, though its interaction with TEI, might predict caregivers' PSS. Results: Data yielded a direct relationship between CBP and TEI, and caregivers' PSS; however, no interaction effect was observed. These data reflect the fact that caregivers of children with more behaviour problems are at greater risk for psychological distress, as are caregivers with lower TEI. The relationship between CBP and PSS, however, was not differentially affected by caregivers' TEI. Conclusions: These findings, which implicate lower TEI and greater CBP as risk factors for psychological maladjustment in caregivers of children with ASD, might inform the design and delivery of tailored stress management interventions.